Impact of allogeneic haematopoietic stem cell transplantation in patients with abnl(17p) acute myeloid leukaemia. (21st February 2013) - Mohr, Brigitte; Schetelig, Johannes; Schäfer‐Eckart, Kerstin; Schmitz, Norbert; Hänel, Mathias; Rösler, Wolf; Frickhofen, Norbert; Link, Hartmut; Neubauer, Andreas; Schuler, Ulrich; Platzbecker, Uwe; Middeke, Jan M.; et al.
Summary: The role of allogeneic stem cell transplantation (HSCT) as compared to chemotherapy in acute myeloid leukaemia (AML) patients with abnormalities of chromosome 17p [abnl(17p)] has not yet been defined. Therefore, we analysed 3530 AML patients treated in three randomized, prospective, controlled clinical trials and compared post‐remission therapies using a multivariate Cox regression analysis to determine whether allogeneic HSCT is superior than chemotherapy in overcoming the detrimental impact of patients with abnl(17p) AML. One hundred and forty‐three patients (4%) were identified with abnl(17p) AML. All patients had received intensive induction chemotherapy. Forty‐seven patients with a median age of 54 years (18–69 years) proceeded to allogeneic HSCT in first or second remission. The 3‐year overall survival (OS) rate for the entire cohort of patients was 4% [95% confidence interval (CI), 1–7%]. OS and event‐free survival at 3 years, calculated from the day of HSCT, was 11% (95% CI, 2–20%) and 6% (95% CI, 0–13%), respectively. Multivariate Cox regression analysis showed no benefit of allogeneic HSCT compared to chemotherapy (Hazard Ratio 0·97, 95% CI 0·56–1·67, P  = 0·9). In conclusion, allogeneic HSCT does not improve survival in patients with abnl(17p) AML as compared to other adverse cytogenetic risk abnormalities.